The role of cooperatives in LDCs - Johannes Kuhn (Intereconomics, 1974)
Socio-economic conditions in LCDs generally are featuring a more or less naked dualism. The question has to be asked whether cooperatives could not be used as tools for dismantling this dualism.
Keywords: 330; Cooperatives